Foliar application of zinc improves morpho-physiological and antioxidant defense mechanisms, and agronomic grain biofortification of wheat (Triticum aestivum L.) under water stress - Sattar, Abdul; Wang, Xiukang; Ul-Allah, Sami; Sher, Ahmad; Ijaz, Muhammad; Irfan, Muhammad; Abbas, Tahira; Hussain, Sajjad; Nawaz, Farukh; Al-Hashimi, Abdulrahman; Al Munqedhi, Bandar M; Skalicky, Milan (Saudi journal of biological sciences, 2022)
Agronomic biofortification with zinc (Zn) may be engaged to improve the nutritious value of food crops along-with tolerance to water deficit conditions. The Zn may increase plant resistance to water stress by boosting physiological and enzymatic antioxidants defense mechanisms. Major objective of this study was to investigate the effect of foliar applied Zn on grain zin biofortification and drought tolerance in wheat. Treatments include application of Zinc at terminal growth phases (BBCH growth stage 49 and BBCH growth stage 65) with five levels: 0 (control-ck), water spray, 5, 10 and 15 mM under two levels of water regimes; well-watered (where 80% water holding capacity (WHC) was maintained in the soil) and water stress, (where 40% WHC was maintained in the soil). Results revealed that water stress significantly reduced relative water contents, gas exchange attributes, plant height, yield and yield related attributes of wheat. In contrast, hydrogen peroxide, free proline levels, activities of malondialdehyde, and concentration of soluble protein were markedly increased under water stress condition. Application of various levels of Zn significantly improved the CAT, SOD, POD and ASP activities at 40% WHC compared with control treatment. Foliarly applied 10 and 15 mM Zn predominantly reduced the damaging impact of water stress by improving the plant status in the form of plant height, RWC and gas exchange attributes. Likewise, wheat plant treated with 10 mM Zn under water stress condition increased the grain yield by improving number of grains per spike, 100 grain weight and biological yield compared with control. Moreover, increasing Zn levels also increased Zn concentration in grains and leaves. Overall, this study suggests that optimum level of Zn (10 mM) might be promising for alleviating the adverse impacts of water stress and enhance the grain biofortification in wheat.
Keywords: Water stress; Biofortification; Oxidative stress; Zinc; Gas exchange attributes